Cytokine gene regulation by PGE2, LTB4 and PAF - M. Rola-Pleszczynski; J. Stankova (Mediators of Inflammation)
The initial response of the host to noxious stimuli produces a nonspecific inflammatory response. A more specific immune response is believed to be modulated by two classes of molecules: lipid mediators (PG, LT and PAF) and cytokines, synthesized by phagocytes and parenchyreal cells. In this review we discuss the increasing evidence of the interrelationship between eicosanoids, PAF and cytokines: IL-1 and TNF induce PG synthesis in various cells and PG, in turn, modulate cytokine production. We focused on the regulatory effects of LTB4, PGE2 and PAF on cytokine gene expression.